(untitled) (International journal of artificial intelligence, 2026)
This article highlights the pedagogical conditions for the use of integrative educational technologies in the preschool education system, their influence on children's development, and their role in increasing the effectiveness of education. The significance of classes organized on the basis of an integrative approach in the development of cognitive activity, creative thinking, and communicative skills in children is analyzed.